PENILAIAN ASET SUMBER DAYA MANUSIA - Helmi Buyung Aulia Safrizal (Trunojoyo University of Madura, 2011)
Human Resource valuation or human assets refers to the measurement and identification of human resources value and information communication to concerned parties. The need for meeting the rising future business opportunities and simultaneously improve and maintain upon the current performance levels has now compelled organizations to consciously look into manpower as a future success leverageHuman assets are in intangible form and are within the inside of human resources. Human assets consisted of intellectual capital, social capital, emotional capital and spiritual capital. There are three main approaches in assessing the human resource asset that is cost-based approach, monetary value based approach and non-monetary value based approach